Characterization and Functional Analysis of 4-Coumarate:CoA Ligase Genes in Mul-berry. - Chuan-Hong Wang; Jian Yu; Yu-Xiang Cai; Pan-Pan Zhu; Chang-Ying Liu; Ai-Chun Zhao; Rui-Hua Lü; Meng-Jiao Li; Feng-Xiang Xu; Mao-De Yu (PLoS ONE)
A small, multigene family encodes 4-coumarate:CoA ligases (4CLs) that catalyze the ligation of CoA to hydroxycinnamic acids, a branch point directing metabolites to flavonoid or monolignol pathways. In this study, we characterized four 4CL genes from M. notabilis Genome Database, and cloned four Ma4CL genes from M. atropurpurea cv. Jialing No.40. A tissue-specific expression analysis indicated that Ma4CL3 was expressed at higher levels than the other genes, and that Ma4CL3 was strongly expressed in root bark, stem bark, and old leaves. Additionally, the expression pattern of Ma4CL3 was similar to the trend of the total flavonoid content throughout fruit development. A phylogenetic analysis suggested that Mn4CL1, Mn4CL2, and Mn4CL4 belong to class I 4CLs, and Mn4CL3 belongs to class II 4CLs. Ma4CL genes responded differently to a series of stresses. Ma4CL3 expression was higher than that of the other Ma4CL genes following wounding, salicylic acid, and ultraviolet treatments. An in vitro enzyme assay indicated that 4-coumarate acid was the best substrate among cinnamic acid, 4-coumarate acid, and caffeate acid, but no catalytic activity to sinapate acid and ferulate acid. The results of subcellular localization experiments showed that Ma4CL3 localized to the cytomembrane, where it activated transcription. We used different vectors and strategies to fuse Ma4CL3 with stilbene synthase (STS) to construct four Ma4CL-MaSTS co-expression systems to generate resveratrol. The results indicated that only a transcriptional fusion vector, pET-Ma4CL3-T-MaSTS, which utilized a T7 promoter and lac operator for the expression of MaSTS, could synthesize resveratrol.